2020
DOI: 10.1021/acs.analchem.9b05175
|View full text |Cite
|
Sign up to set email alerts
|

Highly Chemoselective Self-Calibrated Fluorescent Probe Monitors Glutathione Dynamics in Nucleolus in Live Cells

Abstract: The redox-regulator glutathione (GSH) maintains a specific redox potential to sustain routine cellular activity from oxidative damage. In the early stage of the cell cycle process, the glutathione levels increase in the nuclei for protecting the DNA replication process from reactive oxygen species (ROS). In the first attempt, we developed a new ratiometric fluorescent probe that has provided information about glutathione levels in the nuclei. The UV−vis. absorption of probe GScp has shown a hypsochromic shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Nowadays, there are various methods to achieve the detection of redox processes, such as fluorescence, colorimetry, electrochemical methods, chemiluminescence (CL), etc. For example, a fluorescent probe (GScp) was used to monitor cross-talk between GSH/H 2 O 2 , and the carbon dots were introduced to detect HOCl/ClO – and AA in living cells by fluorescence and colorimetric dual-mode methods . In addition, an electro-optical nanoprobe was fabricated to reveal the oxidative response and antioxidant levels in cancer cells, and a CL sensor (Au@BSA NCs-Cu 2+ ) was developed for the detection of GSH with the CL intensity enhanced after introducing calcein–H 2 O 2 into CL sensor and the intensity decreased after adding GSH .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are various methods to achieve the detection of redox processes, such as fluorescence, colorimetry, electrochemical methods, chemiluminescence (CL), etc. For example, a fluorescent probe (GScp) was used to monitor cross-talk between GSH/H 2 O 2 , and the carbon dots were introduced to detect HOCl/ClO – and AA in living cells by fluorescence and colorimetric dual-mode methods . In addition, an electro-optical nanoprobe was fabricated to reveal the oxidative response and antioxidant levels in cancer cells, and a CL sensor (Au@BSA NCs-Cu 2+ ) was developed for the detection of GSH with the CL intensity enhanced after introducing calcein–H 2 O 2 into CL sensor and the intensity decreased after adding GSH .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure A, the fluorescence intensity of the probe was maintained above 85% while it was irradiated by a xenon lamp within 1 h, which indicated that the fluorescent probe had good photostability. Then, as shown in Figure B, the time-dependent course test showed that the probe could fast respond to pH value changes in less than 30 s. Last but not least, reversibility , is one of the evidences of excellent fluorescent probes. The fluorescence intensity of the probe was measured for six cycles while the pH value changes from 3.0 to 10.0.…”
Section: Resultsmentioning
confidence: 86%
“…By contrast, 2b maintained the decrease in GSH levels for 24 h, indicating serious destruction of the cellular antioxidant system. Furthermore, glutathione ethyl ester (GSH‐OEt), [ 65 ] a cell‐permeable GSH precursor that acts as a powerful antioxidant by intracellular hydrolysis of GSH, barely affected 1b‐ and 2b ‐induced cytotoxicity but almost completely avoided 2a ‐induced cytotoxicity (Figure 5I). This suggests that in the presence of GPX4 inhibition, high levels of GSH are insufficient for rescuing ferroptotic cell death.…”
Section: Resultsmentioning
confidence: 99%
“…This was further confirmed by supplementation with the GSH biosynthesis precursor N ‐acetyl‐ l ‐cysteine (NAC) and promoter ( R )‐(+)‐α‐lipoic acid (LPA). [ 66 ] Additionally, l ‐buthionine sulfoximine(BSO), a GSH biosynthesis inhibitor, [ 65 ] exacerbated cytotoxicity via irreversible inhibition of γ‐glutamylcysteine synthetase (Figure S27, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%